2019
DOI: 10.1109/access.2019.2940866
|View full text |Cite
|
Sign up to set email alerts
|

AffectiveWall: Designing Collective Stress-Related Physiological Data Visualization for Reflection

Abstract: Excessive workplace stress affects the individual's health as well as social collaborations, so the management of stressors is essential. However, an individual worker who only subjectively reflects on his or her individual and social stressors may misinterpret them, and thus not be able to manage them. This paper aims at engaging workplace stress reflection on objective stress-related physiological data using a shared display, which provides an anonymous view of the individual stress-related physiological sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…[77], [89], [90], [91], [118], [133], [136] Co-located [2,63,93] , [17], [32], [40], [46], [54], [87], [88], [100], [110], [116], [121], [122], [123], [142] [37], [55], [98], [112], [119], [120], [83], [130] Synchronous Asynchronous…”
Section: Physical Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…[77], [89], [90], [91], [118], [133], [136] Co-located [2,63,93] , [17], [32], [40], [46], [54], [87], [88], [100], [110], [116], [121], [122], [123], [142] [37], [55], [98], [112], [119], [120], [83], [130] Synchronous Asynchronous…”
Section: Physical Contextmentioning
confidence: 99%
“…In symmetrical systems, it was most common for users to receive biofeedback about their own physiological state together with that of other users' (n=14; [2,52,54,67,70,72,73,75,77,85,95,116,119,121]). In 12 studies, users only received feedback about states of co-users and not their own [3,29,30,45,55,65,87,91,94,110,125,133], while in four studies only aggregated measures of physiology were shown to both players [83,100,107,142]. Six studies combined the sharing physiology of all users with additional aggregated measures like average metrics [17] and synchrony level between users [46,60,61,82,113].…”
Section: Articulating the Physiological-social Interaction Spacementioning
confidence: 99%
See 3 more Smart Citations